A Two-Dimensional Electron Gas as a Sensitive Detector for Time-Resolved Tunneling Measurements on Self-Assembled Quantum Dots - Reuter Dirk; Wieck Andreas; Geller Martin; Marquardt Bastian; Lorke Axel (Nanoscale Research Letters, 2010)
Abstract A two-dimensional electron gas (2DEG) situated nearby a single layer of self-assembled quantum dots (QDs) in an inverted high electron mobility transistor (HEMT) structure is used as a detector for time-resolved tunneling measurements. We demonstrate a strong influence of charged QDs on the conductance of the 2DEG which allows us to probe the tunneling dynamics between the 2DEG and the QDs time resolved. Measurements of hysteresis curves with different sweep times and real-time conductance measurements in combination with an boxcar-like evaluation method enables us to unambiguously identify the transients as tunneling events between the s- and p-electron QD states and the 2DEG and rule out defect-related transients.